2014 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM 2014) 2014
DOI: 10.1109/asonam.2014.6921619
|View full text |Cite
|
Sign up to set email alerts
|

Online social media in the Syria conflict: Encompassing the extremes and the in-betweens

Abstract: Abstract-The Syria conflict has been described as the most socially mediated in history, with online social media playing a particularly important role. At the same time, the everchanging landscape of the conflict leads to difficulties in applying analytical approaches taken by other studies of online political activism. Therefore, in this paper, we use an approach that does not require strong prior assumptions or the proposal of an advance hypothesis to analyze Twitter and YouTube activity of a range of prota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Starting from 512 radicalised Twitter accounts, manually identified in the work of O'Callagan [26], they collected their followers, filtered those based in Europe and determined whether those followers were radicalised based on two hypothesis: (i) use of pro-ISIS terminology, a lexicon was generated to test this hypothesis, and (ii) content shared from pro-ISIS accounts. Their filtering process lead to the study of 727 pro-ISIS Twitter accounts and their complete timelines.…”
Section: Computational Approachesmentioning
confidence: 99%
“…Starting from 512 radicalised Twitter accounts, manually identified in the work of O'Callagan [26], they collected their followers, filtered those based in Europe and determined whether those followers were radicalised based on two hypothesis: (i) use of pro-ISIS terminology, a lexicon was generated to test this hypothesis, and (ii) content shared from pro-ISIS accounts. Their filtering process lead to the study of 727 pro-ISIS Twitter accounts and their complete timelines.…”
Section: Computational Approachesmentioning
confidence: 99%
“…For instance, although O'Callaghan et al [11] did not necessary label Twitter users as being pro or anti-ISIS (as we do in this paper), the authors instead clustered Twitter users collected from Twitter lists related to the Syria conflict into high-modularity clusters. The authors subsequently identified a cluster of 'jihadist' users, which contained those who support ISIS.…”
Section: Related Workmentioning
confidence: 99%
“…11 This includes: number of followers, number of followee, number of hashtags, number of mentions (i.e., @user), favourites count, status count, profile description, and geographic location. The notion behind using these features for radicalisation detection is that users of a certain radicalisation stance are more likely to interact with other users of the same stance than with users from a different stance, as we discussed in our previous work [14].…”
Section: Baseline Featuresmentioning
confidence: 99%
“…For all other uses, contact the owner/author(s). sen by an expert panel as search queries; 2) collecting the random sample without specified search terms and extracting appropriate data [2]; 3) collecting from specific users that are known to be contributing to the debate [3].…”
Section: Introductionmentioning
confidence: 99%